PENGEMBANGAN APLIKASI UNTUK MEMBANTU ANALISIS DATA SURVEY TENTANG PENTINGNYA PROGRAM PELATIHAN BIDANG TIK BAGI GURU BERBASIS “USER NEEDS ASSESMENT “ - Agus Aan Jiwa Permana (LPPM Universitas Dhyana Pura, 2017)
ABSTRACT Information and Communication Technology (ICT) in general are all technologies related to thecollection, collection, processing, storage, dissemination, and presentation of information widelyapplied in all fields, one of them in education. Teachers are professional educators who have animportant role and role in the intellectual life of the nation. Regulation of the Minister of NationalEducation No. 16 of 2007 dated May 4, 2007 on the standard of academic qualification andcompetence of teachers, especially on the Competency Standards of Elementary Teachers who inPedagodic Competence is utilizing ICT for learning purposes and on Professional Competence isutilizing ICT to communicate and develop themselves. But in fact many teachers in Sukasadadistrict, Buleleng who still do not understand the use of technology. Based on the description abovethe information system is needed survey through questionnaire related to the extent of the teacherskills in the field of ICT. In the analytical process an application is needed to help providerecommendations on the need for ICT training for teachers in schools.Keywords : Information and Communication Technology Training, Teacher CompetencyStandards, Pedagogic Competencies, Questionnaire Analysis, Skills Survey ABSTRAK Teknologi Informasi dan Komunikasi (TIK) secara umum adalah semua teknologi yangberhubungan dengan pengambilan, pengumpulan, pengolahan, penyim-panan, penyebaran, danpenyajian informasi yang banyak diterapkan di segala bidang, salah satunya di bidang pendidikan.Guru adalah pendidik professional yang mempunyai tugas dan peran penting dalam mencerdaskankehidupan bangsa. Peraturan Menteri Pendidikan Nasional Nomor 16 Tahun 2007 tanggal 4 Mei2007 tentang standar kualifikasi akademik dan kompetensi Guru, khususnya pada StandarKompetensi Guru SD yang pada Kompetensi Pedagodik adalah me-manfaatkan TIK untukkepentingan pembelajaran dan pada Kompetensi Profesional adalah memanfaatkan TIK untukberkomunikasi dan mengembangkan diri. Namun kenyataannya banyak guru di kecamatanSukasada, Buleleng yang masih belum memahami penggunaan teknologi. Berdasarkan uraian diatas sistem informasi sangat diperlukan survey melalui kuisioner terkait sejauh mana keterampilan gurudi bidang TIK. Dalam proses analisi diperlukan sebuah aplikasi untuk membantu memberikanrekomendasi tentang perlunya diadakan pelatihan TIK untuk guru di sekolah.Kata kunci: Pelatihan Teknologi Informasi dan Komunikasi, Standar Kompetensi Guru, Kompetensi Pedagodik, Analisis Kuisioner, Survey Keterampilan